Oil palm adoption, household welfare and nutrition among smallholder farmers in Indonesia - Michael Euler; Vijesh Krishna; Stefan Schwarze; Hermanto Siregar; Matin Qaim (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
The recent expansion of oil palm in Indonesia is largely smallholder-driven. However, its socio-economic implications are under-examined. Analyzing farm-household data from Jambi Province, Sumatra, oil palm adoption is found to have positive consumption and nutrition effects. However, these effects are largely due to farm size expansion that is associated with oil palm adoption. Potential heterogeneity of effects among oil palm adopters is examined using quantile regressions. While nutrition effects of oil palm adoption are found to be homogenous across quantiles, the effects on non-food expenditure are expressed more strongly at the upper end of the expenditure distribution.
urn:nbn:de:gbv:7-webdoc-3955-0
Keywords: 330; non-food cash crops; oil palm expansion; smallholder livelihoods; quantile regression; Indonesia